2011
DOI: 10.1021/nn2016716
|View full text |Cite
|
Sign up to set email alerts
|

Shape-Controlled Colloidal Synthesis of Rock-Salt Lead Selenide Nanocrystals

Abstract: Developing simple synthetic methods to control the size and morphology of nanocrystals is an active area of research as these parameters control the material's electronic and optical properties. For a semiconductor with a symmetrical crystal structure such as lead selenide, anisotropic colloidal growth has been previously accomplished via the use of templates, seeds, or by block assembly of smaller, symmetrical subunits. Here, we present a simple method to create monodisperse lead selenide nanorods and multipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 39 publications
(65 reference statements)
2
18
1
Order By: Relevance
“…They include colloidal synthesis [10], solution-liquid-solid [12] methods and even oriented attachment of lead salt nanocrystals [8]. Nowadays it is not only possible to grow a nanowire a few nm thin [13], but also to control its shape [14][15][16], size [17] and growth direction [18]. Nonetheless, theoretical modelling of lead chalcogenide NWs is quite challanging due to the multivalley band structure and strong intervalley coupling in these systems.…”
Section: Introductionmentioning
confidence: 99%
“…They include colloidal synthesis [10], solution-liquid-solid [12] methods and even oriented attachment of lead salt nanocrystals [8]. Nowadays it is not only possible to grow a nanowire a few nm thin [13], but also to control its shape [14][15][16], size [17] and growth direction [18]. Nonetheless, theoretical modelling of lead chalcogenide NWs is quite challanging due to the multivalley band structure and strong intervalley coupling in these systems.…”
Section: Introductionmentioning
confidence: 99%
“…35 Jawaid et al showed that PbSe rods and multipods of nearly 4.5 nm diameter can be synthesized in the inadvertently oxidated polyunsaturated solvent. 36 Recently, Murray's group has reported PbSe NRs of ∼4 nm diameter by using a new phosphine selenide precursor. 37 However, none of the PbSe NRs reported previously have been employed in solar cells likely due to their large diameters (>4 nm), resulting in an unsuitably small bandgap for photovoltaic application.…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] In addition, the large nonlinearity of PbSe NCs has also been reported, thereby rendering them attractive materials in nonlinear optics. [14] Currently, a considerable number of methods have been developed to fabricate PbSe NCs with various sizes and morphologies, including spheres, [15][16][17] cubes, [15,18,19] multipods, [18,20] rods, [18,21] octahedrons, [22] wires, [18,22] and rings. [22] The available synthetic methods generally use stabilizing ligands such as trioctylphosphine (TOPO) and lead sources such as lead acetate trihydrate or lead oxides.…”
Section: Introductionmentioning
confidence: 99%